2012
DOI: 10.1016/j.neuron.2012.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Therapeutic Reversal of Huntington's Disease by Transient Repression of Huntingtin Synthesis

Abstract: SUMMARY The primary cause of Huntington’s disease (HD) is expression of huntingtin with a polyglutamine expansion. Despite an absence of consensus on the mechanism(s) of toxicity, diminishing the synthesis of mutant huntingtin will abate toxicity if delivered to the key affected cells. With antisense oligonucleotides (ASOs) that catalyze RNase H-mediated degradation of huntingtin mRNA, we demonstrate that transient infusion into the cerebral spinal fluid of symptomatic HD mouse models not only delays disease p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
714
1
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 655 publications
(762 citation statements)
references
References 48 publications
25
714
1
8
Order By: Relevance
“…ASO-mediated decrease of huntingtin protein in a mouse model of Huntington's disease delayed and even reversed pathology. This effect persisted for months after the mRNA and protein levels of huntingtin returned to baseline, indicating a robust and long-lasting effect [85]. ASOs also decreased mutant SOD1 in both the brain and the CSF in a mouse model of ALS [87].…”
Section: Rnai and Antisense Oligonucleotide Therapiesmentioning
confidence: 90%
See 2 more Smart Citations
“…ASO-mediated decrease of huntingtin protein in a mouse model of Huntington's disease delayed and even reversed pathology. This effect persisted for months after the mRNA and protein levels of huntingtin returned to baseline, indicating a robust and long-lasting effect [85]. ASOs also decreased mutant SOD1 in both the brain and the CSF in a mouse model of ALS [87].…”
Section: Rnai and Antisense Oligonucleotide Therapiesmentioning
confidence: 90%
“…These techniques target a highly specific sequence present in the mRNA of a target protein, leading to decreased translation (RNAi) or degradation of the mRNA transcript (RNAi/ASO) [84][85][86]. RNAi techniques can preferentially decrease the expression of a mutant allele over the wild-type transcript, as base pair mismatches between the siRNA and target RNA inhibit their binding and subsequent degradation [86].…”
Section: Rnai and Antisense Oligonucleotide Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A long-standing idea in HD therapy development has centered around the clearance of mHTT, and previous studies have shown attenuated HD phenotypes upon genetic reduction of mHTT [3]. Recently, substantial progress has been made using anti-sense oligonucleotides (ASOs) to reduce mHTT in preclinical models of HD [4], however, the challenge of delivering ASOs clinically has precluded its widespread use and application. Therefore, pharmacological interventions that can be more easily delivered while similarly reducing mHTT levels are especially appealing.…”
Section: In a Paper Recently Published Inmentioning
confidence: 99%
“…ASOs for use outside of the nervous system have been developed for multiple diseases and recently resulted in an US Food and Drug Administrationapproved drug for familial hypercholesterolemia (mipomersen) [18]. The promise of using ASOs to treat neurodegenerative diseases has been greatly bolstered by recent demonstrations of wide spread distribution of ASOs throughout the brain and spinal cord when delivered to the cerebrospinal fluid (CSF) [19][20][21].…”
mentioning
confidence: 99%